Echocardiographic flow pattern of patent ductus arteriosus: a guide to indomethacin treatment in premature infants. Issue 3 (1st November 1999) - Su, Bai-Horng; Peng, Ching-Tien; Tsai, Chang-Hai
Abstract : AIM: To compare the efficacy and safety of an indomethacin treatment strategy based on serial echocardiographic measurement of patent ductus arteriosus (PDA) flow pattern with a standard protocol. METHODS: Neonates weighing less than 1500 g at birth, who required respiratory support, and who had developed symptomatic PDA, were studied. PDA was confirmed in all infants using colour Doppler echocardiography, and serial observations of the ductal flow pattern were made. Infants randomly assigned to receive conventional indomethacin treatment (protocol group) were given an initial dose of 0.2 mg/kg, followed by 0.1 or 0.2 mg/kg, depending on age, 12 hourly for two further doses, and were eligible for a second course. Those randomly assigned to the ductal flow pattern assessment (ECHO group) received further doses of indomethacin after 24 hours, only if their flow pattern was "pulsatile" or "growing." RESULTS: There was no significant difference in the primary outcome measures between the two groups. The closure rate was 89.1% and 87.2%, respectively, in the protocol and ECHO groups. The mean (SD) doses of indomethacin were significantly higher in the protocol group: 3.2 (1.4) doses compared with 1.6 (0.9) doses. There was a significantly higher incidence of hypoglycaemia, impaired urine output, and gastrointestinal bleeding in the protocol group. CONCLUSIONS: An indomethacin treatment strategy for PDA based on measurement of the ductal flow pattern is associated with a reduction in the total doses of indomethacin administered, and a reduced rate of complications, compared with a conventional protocol. There is no difference in closure rate.